2015
DOI: 10.4137/sart.s23546
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian Offender Mental Health and Addiction Study – Design and Implementation of a National Survey and Prospective Cohort Study

Abstract: The Norwegian prison inmates are burdened by problems before they enter prison. Few studies have managed to assess this burden and relate it to what occurs for the inmates once they leave the prison. The Norwegian Offender Mental Health and Addiction (NorMA) study is a large-scale longitudinal cohort study that combines national survey and registry data in order to understand mental health, substance use, and criminal activity before, during, and after custody among prisoners in Norway. The main goal of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 26 publications
1
38
0
6
Order By: Relevance
“…655 in the United States, 468 in Russia, 163 in Mexico, 114 in Canada) (WPB, 2019). In Norway, prison beds are spread across the country, to allow most prisoners to preserve geographical closeness to friends and family during prison (Bukten et al, 2015). All prisons are publicly funded and are categorized into high-security (almost two-thirds of prisons), low-security, or transitional housing units.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…655 in the United States, 468 in Russia, 163 in Mexico, 114 in Canada) (WPB, 2019). In Norway, prison beds are spread across the country, to allow most prisoners to preserve geographical closeness to friends and family during prison (Bukten et al, 2015). All prisons are publicly funded and are categorized into high-security (almost two-thirds of prisons), low-security, or transitional housing units.…”
Section: Settingmentioning
confidence: 99%
“…We based this cross-sectional study on self-reported data from the Norwegian Offender Mental Health and Addiction (NorMA) study (Bukten et al, 2015). The NorMA study is a large-scale study that uses national survey data to understand mental health, substance use, and criminal activity before incarceration among people in prison in Norway.…”
Section: Participantsmentioning
confidence: 99%
“…This cross-sectional analysis used a large cohort study of prisoners in Norway, the Norwegian Offender Mental Health and Addiction (NorMA) study, the methodology of which has been described in Bukten, Lund [48]. In the NorMA study, study investigators distributed questionnaires to 57 of 63 Norwegian prisons in 2013 and 2014, and collected self-reported survey data from 1,499 inmates of high security units, low security units, and transitional facilities.…”
Section: Methodsmentioning
confidence: 99%
“…En egen artikkel er publisert for å gi en grundig beskrivelse av NorMA-prosjektet og gjennomføringen av datainnsamlingen [12]. Hele artikkelen er fritt tilgjengelig: http://www.la-press.com/thenorwegian-offender-mental-health-and-addiction-study--design-and-i-article-a5233…”
Section: For Mer Inofrmasjon Om Studienunclassified
“…Resultatene i Tabell 4 viser at om lag en fjerdedel (25%) av innsatte rapporterer lese-og skrivevansker, og at andelen var noe større blant menn (25%) sammenlignet med blant kvinner (15%). Treårig høyskole eller mer 178 (12,8) 13 (13,5) 193 (12,9) Yrkesstatus siste 6 måneder før fengsling Heltidsjobb 461 (33) 21 (21,9) 482 (32,2) Deltidsjobb 133 (9,5) 11 (11,5) 145 (9,7) Under utdanning 125 (…”
Section: Utdanning Og Inntektunclassified